Controlling the transmission of mastitis-causing pathogens across heterogeneous dairy herds - Evans, N; Cronin, D; White, L; Chappell, M; Chapman, M; Godfrey, K (Elsevier, 2016)
Using a mathematical model for the transmission of mastitis-causing pathogens in a dairy herd and parameter estimation, control strategies are derived for a number of different herds. In addition, a single common strategy is derived for control of all of the herds. A key feature of all of the control strategies is that they minimise the combined costs associated with infection and treatment. Only a small decrease in performance results from developing a common strategy.